Penerapan Metode Crossword Puzzle Dalam Mendukung Motivasi Belajar Mata Pelajaran Al-Islam Di SMA Muhammadiyah 4 Surabaya - Arifin, Shokhibul; Mujtahidah, Zulfa Ishlahul (IJoIS: Indonesian Journal of Islamic Studies, 2023)
Students in the Islamic Studies learning are expected to comprehend the taught materials so that they are motivated in their learning. To achieve this learning motivation, research was conducted at Muhammadiyah 4 High School in Surabaya, in the XI grade with a total of 26 students. The research utilized the crossword puzzle teaching method to support students' motivation in the subject of Islamic Studies. This study employed qualitative research with descriptive analysis. The research results indicate that the implementation of the crossword puzzle method is able to support students' motivation in the subject of Islamic Studies. This is evidenced by the observations during the learning process and the interview results from the teacher, in line with the learning motivation indicators during the application of the crossword puzzle method in the classroom. Based on this research, it can be concluded that the application of the crossword puzzle method can support students' learning motivation in the subject of Islamic Studies for the XI grade at Muhammadiyah 4 High School in Surabaya.